KEBIJAKAN PENGAWASAN TERHADAP PRODUK UMKM SEBAGAI UPAYA PERLINDUNGAN PADA KONSUMEN - Siti Mariyam (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
In the market there are many outstanding goods and / or services produced by UMKM. UMKM is indeed a growing business sector in the community that proved able to compete with other business actors. Through the economic policy package of President Joko Widodo, the government encourages the empowerment of UMKM. Although the government encourages the progress and development of UMKM but the circulation of UMKM products should be supervised. This is because there are still many products of UMKM, especially food circulating in the market that has not met the quality standards and labeling, especially labels expired so that this can endanger consumers. Therefore it is necessary to supervise the products of UMKM as an effort to protect the consumer. Supervision includes quality standards, labeling, standard clauses, and advertising. Such supervision is important to protect consumers from loss of goods that do not meet the standards specified in the legislation.